A review of breaking wave force on the bridge pier: Experiment, simulation, calculation, and structural response - Kai Wei; Jie Hong; Mochen Jiang; Wenyu Zhao (Journal of Traffic and Transportation Engineering (English ed. Online), 2022)
In the course of the propagation of waves from the offshore to the nearshore zone, the wave may break due to the shoaling effect. Strong impact forces are observed when the breaking wave acts on the pier of the bridge. This impact force might not only change the dynamic load pattern on the pier but also cause strong structural vibration, which may threaten the driving and structural safety of the bridge. Many studies have been carried out to study the issues in the aspect of wave flume experiment, numerical simulation, calculation of breaking wave force, and random vibration response of the structure. Considering the studies of breaking wave load on bridge piers are lack of systematic summaries, this paper presents a comprehensive and up-to-date literature review of breaking wave research and practice related to bridges. Firstly, a brief introduction is given, which includes recent cases of bridge failures caused by breaking waves. Then, both scientific and technical studies are reviewed, categorized into four aspects: experimental study, numerical simulation, analytical calculation of breaking wave force, and the structural response under breaking wave. Finally, Discussion is provided on four emerging ideas to investigate breaking wave forces on the pier from both science and engineering perspectives.